A longitudinal study characterising a large adult primary ciliary dyskinesia population. Issue 2 (10th June 2016) - Shah, Anand; Shoemark, Amelia; MacNeill, Stephanie J.; Bhaludin, Basrull; Rogers, Andrew; Bilton, Diana; Hansell, David M.; Wilson, Robert; Loebinger, Michael R.
Primary ciliary dyskinesia (PCD) in adults has not been well described. In this retrospective observational study we aimed to characterise a large adult population and identify features associated with disease progression. We retrospectively analysed 151 adult patients at a single tertiary centre at baseline and longitudinally for a median of 7 years. We found significant variation in age at diagnosis (median 23.5 years; range <1–72 years). Older age at diagnosis was associated with impaired baseline forced expiratory volume in 1 s (FEV1 ) (r= −0.30, p=0.01) and increased Pseudomonas aeruginosa colonisation (difference in medians 17 years (95% CI 4.5–20 years); p=0.002). Lung function decline was estimated at FEV1 decline of 0.49% predicted per year. Lung function decline was associated with ciliary ultrastructure, with microtubular defect patients having the greatest decline (p=0.04). High-resolution computed tomography (HRCT) scores of severity of bronchial wall dilatation (p<0.001) and extent of bronchiectasis (p=0.03) additionally showed evidence of modifying FEV1 decline with age. Our study reveals that a large proportion of adult PCD patients are diagnosed late, with impaired FEV1 and increased P. aeruginosa colonisation. Increased disease burden on HRCT and ciliary ultrastructure may predict progressive lung function decline. This study characterises a large adult PCD population, identifies features associated with disease progression and highlights the need for prospective trials to determine whether early diagnosis of high-risk subgroups alongside optimal management can modify disease progression. Increased severity on HRCT and ciliary ultrastructure predict progressive lung function decline in adults with PCD http://ow.ly/4ncpnD